Differentiation Strategy Based on Islamic Economic Values in Enhancing the Competitive Advantage of Dua Berkah Binjai Bakery - Yahman, Qaila Nailaya; Batubara, Chuzaimah; Nurbaiti, Nurbaiti (JURNAL AT-TURAS, 2026)
This study aims to analyze the product differentiation strategy implemented by the Dua Berkah Binjai Bakery SME in enhancing its competitive advantage based on Islamic economic values. The research approach used is a descriptive qualitative method through in-depth interviews, direct observation, and sales document analysis supported by NVivo software. The results of the study indicate that the success of the Dua Berkah Binjai Bakery business is not only determined by product quality, affordable prices, and distribution networks through resellers, but also by the application of Islamic economic values such as honesty, trustworthiness, and the principles of halal and thayyib in the production process. These values create consumer trust, which is an important factor in maintaining customer loyalty. However, this business still faces several challenges, such as limited product innovation, distribution delays, and weak digital branding, which can hinder market expansion. Therefore, this study recommends strengthening product innovation, optimizing digital marketing, and consistently applying Islamic economic principles in business activities in order to increase competitiveness and business sustainability.